Pendidikan sebagai Pilar Peradaban Islam: Studi Dinamika Sosial pada Masa Nabi Muhammad - Wahyu Sihab; Dzulkifli Hadi Imawan (Jurnal Eduslamic, 2025)
This study aims to examine the strategic role of education in shaping Islamic civilization during the time of the Prophet Muhammad, particularly through the social dynamics that took place during the Mecca and Medina periods. This study uses a systematic literature review method, collecting data from various historical literature, classical Islamic education, and current academic sources. The results of the study indicate that education during the time of the Prophet Muhammad SAW not only served as a means of conveying religious teachings but also as an effective instrument of social change. Through a prophetic approach integrated with societal realities, education was able to shape individuals of faith while building a civilized, inclusive, and value-based social system rooted in divine principles. The conclusion of this study emphasizes that education is the main foundation in the process of transforming a jahiliyyah society into an Islamic society that is just and civilized. This prophetic education model is relevant as inspiration for the development of a holistic and transformative contemporary Islamic education system.